2016
DOI: 10.1002/vms3.17
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the canine intestinal microbiota and its modification by pro‐, pre‐ and synbiotics – what is the evidence?

Abstract: Interest in the composition of the intestinal microbiota and possibilities of its therapeutic modifications has soared over the last decade and more detailed knowledge specific to the canine microbiota at different mucosal sites including the gut is available. Probiotics, prebiotics or their combination (synbiotics) are a way of modifying the intestinal microbiota and exert effects on the host immune response. Probiotics are proposed to exert their beneficial effects through various pathways, for example produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
91
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 130 publications
(142 reference statements)
1
91
3
2
Order By: Relevance
“…Overall, the present results show that the administration of prebiotics in certain concentrations might encourage the growth of certain bacterial strains (especially bifidobacteria), which can either be administered simultaneously as synbiotics, or which are already present in the GI tract as part of the endogenous microflora [8]. Bifidobacteria are part of the canine GI microbiota and certain strains might be classified as probiotics [8,13,23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the present results show that the administration of prebiotics in certain concentrations might encourage the growth of certain bacterial strains (especially bifidobacteria), which can either be administered simultaneously as synbiotics, or which are already present in the GI tract as part of the endogenous microflora [8]. Bifidobacteria are part of the canine GI microbiota and certain strains might be classified as probiotics [8,13,23].…”
Section: Resultsmentioning
confidence: 99%
“…Bifidobacteria are part of the canine GI microbiota and certain strains might be classified as probiotics [8,13,23]. Bifidobacterium animals AHC7 has been shown to protect against pathogen-induced NFκB activation in vivo and was able to reduce both the need to administer antimicrobials and the overall duration of illness in acute idiopathic diarrhoea in dogs [24,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota are generally in a state of equilibrium or eubiosis with the host. Alterations in the gut microbiota (dysbiosis) have been associated with pathogenesis of gastrointestinal disease (Schmitz and Suchodolski, 2016). Several studies have now been reported in dogs from various countries, exploring the canine gut bacterial communities Page127 using either traditional culture or novel molecular approaches (Xenoulis et al, 2008 andSuchodolski, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…improvement of gut barrier integrity) in humans 92 and other vertebrates (Montalban-Arques et al, 2015). 98 Schmitz and Suchodolski, 2016; de Godoy et al, 2013). Domestic cats are obligate carnivores but 99 several studies support the hypothesis that microbial fermentation inside the distal gut is 100 significant and beneficial to the host (Rochus et al, 2014).…”
mentioning
confidence: 97%